2011
DOI: 10.1002/pbc.23190
|View full text |Cite|
|
Sign up to set email alerts
|

A novel mutation Gly603Arg of TMPRSS6 in a Korean female with iron‐refractory iron deficiency anemia

Abstract: Iron-refractory iron deficiency anemia (IRIDA) is a rare hereditary form of IDA with autosomal recessive inheritance. IRIDA is characterized by hypochromic microcytic anemia unresponsive to oral iron treatment, low transferrin saturation, and a high level of iron-regulated hormone hepcidin. The genetic background of IRIDA is mutations in the TMPRSS6 gene encoding matriptase-2 (TMPRSS6) that prevent inactivation of hemojuvelin, an activator of hepcidin transcription. We herein report a Korean female with IRIDA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…4 Patients with mutations in Tmprss6 develop a condition referred to as iron-refractory iron-deficiency anemia (IRIDA). [5][6][7][8][9][10][11][12][13][14][15][16] Decreased Tmprss6 activity leads to increased hepcidin expression through the hemojuvelin-dependent pathway; increased hepcidin expression leads to decreased iron absorption and iron-deficiency anemia. Mouse models of Tmprss6 deficiency recapitulate this phenotype.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Patients with mutations in Tmprss6 develop a condition referred to as iron-refractory iron-deficiency anemia (IRIDA). [5][6][7][8][9][10][11][12][13][14][15][16] Decreased Tmprss6 activity leads to increased hepcidin expression through the hemojuvelin-dependent pathway; increased hepcidin expression leads to decreased iron absorption and iron-deficiency anemia. Mouse models of Tmprss6 deficiency recapitulate this phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Ile286 is a highly conserved residue in the first CUB domain of Tmprss6 and is situated within the vicinity of several other IRIDA-associated residues (Figure 2A-C). [5][6][7][8][9][10][11][12][13][14][15][16] Genotyping of all mice from the hem8 x CAST intercross described above revealed that F286/F286 mice had decreased mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH) levels, total hemoglobin levels and hematocrit relative to I286/I286 and I286/F286 mice (Figure 2D,E; data not shown). To assess the in vitro significance of the I286F substitution on Tmprss6 function, we transfected mouse Tmprss6 cDNA expression constructs encoding the I286 or F286 variant into HEK293T cells.…”
Section: Sequencing Of Exons and Exon/intron Junctions Inmentioning
confidence: 99%
“…The active protease is released from the cell membrane into the extracellular medium by proteolytic cleavage within the stem . So far, 34 MT2 mutations have been identified in human patients with IRIDA [Altamura et al, 2010;Beutler et al, 2009;Choi et al, 2011;De Falco et al, 2010;Edison et al, 2009;Finberg et al, 2008;Guillem et al, 2008;Melis et al, 2008;Ramsay et al, 2009b;Sato et al, 2011;Silvestri et al, 2009;Tchou et al, 2009]. These include missense, nonsense, frameshift, and splice junction mutations.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] TMPRSS6, also known as matriptase-2, is a membrane-bound serine protease 19 expressed in hepatocytes that negatively modulates hepcidin production. Mutations of TMPRSS6 in both humans [20][21][22][23][24][25] and mice 26-29 result in excess hepcidin expression and iron-refractory iron deficiency anemia. In vitro, TMPRSS6 cleaves hemojuvelin (HJV) from the plasma membrane.…”
mentioning
confidence: 99%